Executive power in theory and practice - Liebert, Hugh; McDowell, Gary L. , 1949-; Price, Terry L. , 1966- (Jepson studies in leadership, 2012)
Since September 11, 2001, long-standing debates over the nature and proper extent of executive power have assumed a fresh urgency. In this book eleven leading scholars of American politics and political theory address the idea of executive power